The role of orotic acid measurement in routine newborn screening for urea cycle disorders. Issue 3 (30th November 2020) - Staretz‐Chacham, Orna; Daas, Suha; Ulanovsky, Igor; Blau, Ayala; Rostami, Nira; Saraf‐Levy, Talya; Abu Salah, Nasser; Anikster, Yair; Banne, Ehud; Dar, Dalit; Dumin, Elena; Fattal‐Valevski, Aviva; et al.
Abstract: Urea cycle disorders (UCDs), including OTC deficiency (OTCD), are life‐threatening diseases with a broad clinical spectrum. Early diagnosis and initiation of treatment based on a newborn screening (NBS) test for OTCD with high specificity and sensitivity may contribute to reduction of the significant complications and high mortality. The efficacy of incorporating orotic acid determination into routine NBS was evaluated. Combined measurement of orotic acid and citrulline in archived dried blood spots from newborns with urea cycle disorders and normal controls was used to develop an algorithm for routine NBS for OTCD in Israel. Clinical information and genetic confirmation results were obtained from the follow‐up care providers. About 1147986 newborns underwent routine NBS including orotic acid determination, 25 of whom were ultimately diagnosed with a UCD. Of 11 newborns with OTCD, orotate was elevated in seven but normal in two males with early‐onset and two males with late‐onset disease. Orotate was also elevated in archived dried blood spots of all seven retrospectively tested historical OTCD patients, only three of whom had originally been identified by NBS with low citrulline and elevated glutamine. Among the other UCDs emerge, three CPS1D cases and additional three retrospective CPS1D cases otherwise reported as a very rare condition. Combined levels of orotic acid and citrulline in routine NBS can enhance the detection of UCD, especially increasing the screening sensitivity for OTCD and differentiate it from CPS1D. Our data and the negligible extra cost for orotic acid determination might contribute to the discussion on screening for proximal UCDs in routine NBS.